A student solves the following problem: 2(x - 2) + 5x = 24

Step 1: 2x - 4 + 5x = 24

Step 2: 10x - 4 = 24

Step 3: 10x - 4 + 4 = 24 + 4

Step 4: 10x = 28

Step 5: 10x/10=28/10

Step 6: x = 2.8



Where is the mistake? What did the student do incorrectly?

1 answer

The student made a mistake in Step 2. Let's break down the solution to find the error:

  1. Original equation: \(2(x - 2) + 5x = 24\)
  2. Step 1 (Correct): Distributing the 2 gives \(2x - 4 + 5x = 24\).
  3. Step 2 (Incorrect): The student writes \(10x - 4 = 24\), which is wrong. The correct combination of like terms from Step 1 is: \[ 2x + 5x - 4 = 24 \implies 7x - 4 = 24. \]

So instead of \(10x - 4 = 24\), it should have been \(7x - 4 = 24\).

Continuing from this correct step: 4. Step 3 (incorrect based on previous error): The equation would instead be: \[ 7x - 4 + 4 = 24 + 4 \implies 7x = 28. \] 5. Step 4 (now requires correction): Now divide both sides by 7: \[ x = \frac{28}{7} = 4. \]

Thus, the correct solution is \(x = 4\), not \(x = 2.8\). The error occurred in Step 2 where the student incorrectly combined the coefficients of \(x\).

Similar Questions
  1. A student solves the following equation:Problem: 2(x−3)+3x=19 Step 1: 2x−6+3x=19 Step 2: (2x+3x)−6=19 Step 3: 5x−6=19
    1. answers icon 43 answers
  2. A student solves the following equation:Problem: 2(x−3)+3x=19 Step 1: 2x−6+3x=19 Step 2: (2x+3x)−6=19 Step 3: 5x−6=19
    1. answers icon 1 answer
  3. A student solves the following equation:Problem: 2(x−3)+3x=19 Step 1: 2x−6+3x=19 Step 2: (2x+3x)−6=19 Step 3: 5x−6=19
    1. answers icon 1 answer
  4. A student solves the following equation:Problem: 2(x−3)+3x=19 Step 1: 2x−6+3x=19 Step 2: (2x+3x)−6=19 Step 3: 5x−6=19
    1. answers icon 1 answer
more similar questions